Urgensi Tasawuf dalam Membangkitkan Kesadaran Spiritual Bagi Masyarakat Modern - Aminudin Aminudin (Farabi, 2020)
This article will examine the urgency of Sufism in awakening the spiritual awareness of modern society. Sufism for modern society is very important, because society has been trapped in a rational mindset and has abandoned the inner dimension, giving birth to a materialist and hedonistic lifestyle, meaning that people only think about worldly life without paying attention to the life of the ukhrawi. Therefore spiritual awareness is needed to overcome these problems. Why does Sufism emphasize spirituality in the various aspects? This is because the masters of Sufism, whom we call sufis, believe in the superiority of spirit over the body; believe in the spiritual world rather than the material world. Sufism is also often identified with ihsan, which is the highest stage a Muslim must take to reach his God. And as for the characteristics of Sufism is an increase in awareness of the importance of morality/ethics.